Improving Students’ Reading Ability through the Power of Two Strategy and Google Classroom - Ginting, Realita Br (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The lack of mastery of reading skills in learning English is a problem faced by the tenth-grade students Accounting class in SMKN 2 Singkawang especially to determine the main idea and evaluate specific details in narrative text. This research aim to find the effect of The Power of Two Strategy and Google Classroom to improve students’ reading ability. This research was conducted at SMKN 2 Singkawang, especially among the tenth-grade students of Accounting class. The researcher applied Classroom Action Research (CAR) by conducting two cycles and three meetings in each cycle. The data was collected from 35 tenth-grade students in Accounting class. In collecting data, the researcher used reading tests, observation checklists and field notes. For the data analysis researcher used quantitative and qualitative data. The instrument used to collect data was a reading test. The results of the research in the first and second cycles involved seventy-three and seventy-eight. The finding of this research showed that The Power of Two Strategy and Google Classroom were effective in improving student’s reading ability in enhancing student’s reading ability.